Inhaled Formaldehyde Induction Effect on Urea and Creatinine Levels of Wistar Rats (Rattus Norvegicus) - Ramadhita, Nova Izza Salsa; Lestarini, Ima Arum; Wedayani, Anak Agung Ayu Niti; Punagi, Abdul Qadar; Pieter, Nova Audrey Luetta; Cangara, Muhammad Husni (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Formaldehyde is a chemical substance that has the molecular formula H2-C=O. These chemicals are frequently present in the form of contaminants in the outdoor environment. Previous research has been undertaken to investigate the effects of formaldehyde inhalation on various organs such as the nasopharynx, upper respiratory tract, and lungs. The purpose of this study is to determine the effect of inhaled formaldehyde exposure on kidney function. The parameters of the kidney function tests that were measured were urea and creatinine levels in the rat's blood serum. For 16 weeks, 12 male Wistar rats were used in an experimental investigation with a post-test-only control group design. The rats were divided randomly control and treatment groups. Treatment group exposed to 10% formaldehyde levels as high as 40 ppm by inhalation. Blood serum samples were obtained through the retro orbit at week 16 and analyzed using a UV VIS spectrophotometer. According to data analysis utilizing the Independent T-test, there was a significant difference in the urea content test data (p < 0.05). Mann-Whitney analysis of creatine data revealed that there is no significant difference between the groups. From the statistical analysis, it can be concluded that formaldehyde exposure has an effect on increasing urea levels and has no effect on creatinine levels.